The relationship between corporate social responsibility, business credit for individuals, entrepreneurship, and enhancing the performance of small and medium enterprises - Ummi, Nurul; Katili, Putiri Bhuana; Setiawan, Hadi (Journal Industrial Servicess, 2023)
The growth of small and medium-scale industries has significantly influenced regional economies. These industries, spanning from food production, handicrafts, furniture, to textiles and garment manufacturing, play a crucial role in addressing unemployment rates and bolstering regional economic development. To support small and medium enterprises (SMEs), the government has introduced the People's Business Credit Program (KUR). Besides the KUR program, SMEs receive capital aid and guidance from neighboring companies through what is commonly known as Corporate Social Responsibility (CSR). This study aims to explore the relationship between CSR assistance, KUR, and entrepreneurship in enhancing SME performance. Employing the Structural Equation Modeling (SEM) method, the research investigates causal links between independent and dependent variables, assessing the validity and reliability of the research instrument overall. SEM facilitates the examination of intricate variable relationships to provide an overarching view of the model. Upon data collection and analysis, this study concludes that there exists a causal relationship between CSR and KUR in relation to entrepreneurship, with a total effect value of 0.36. Furthermore, there is a correlation between CSR, KUR, and entrepreneurship, contributing to the enhancement of SME performance, with an indirect effect value of 0.25.